THE INFLUENCE OF SCIENCE LEARNING INTRODUCING PLANT PARTS ON THE COGNITIVE DEVELOPMENT OF EARLY CHILDREN IN TK IT NADAASHOBAH - Titien Ruswanti; Ruqoyyah Fitri (Adisam Publisher, 2024)
This study aims to examine the impact of nature-based science learning on the cognitive development of early childhood students at TK IT Nada Ashobah Wiyung Surabaya. The research method used is a quasi-experimental design with a one- group pretest-posttest design. The population in this study consists of all group B children at TK IT Nada Ashobah, totaling 15 children. The sampling technique used is saturated sampling. The sample consists of 15 group B children. The results show a significant improvement in children's understanding of plant parts after the treatment. The pretest indicated that most children were in the